Onomatopoeia Dalam Puisi Pilihan Oleh Edgar Allan Poe - Sabrina, Fira (CV. Kalimasada Group Profesional, 2023)
Background of this research is the existence of onomatopoeia in Edgar Allan Poe’s selected poems namely “The Bells” and “The Raven”. The writer uses Ullman’s theory as a reference to analyze the types of onomatopoeia and uses contextual meaning in interpreting the word onomatopoeia in context. The purpose of this study is to find the types of onomatopoeia and also to describe the contextual meaning of onomatopoeia words in selected poems by Edgar Allan Poe. Descriptive Qualitative method used in this research. The analysis begins by identifying words that are onomatopoeic and grouped based on Ullman's theory, namely primary (PO) and secondary (SO) types, then, identifying contextual meanings. This research resulted in 26 words, 15 words in the poem